Significance and survival of enterococci during the house fly development - Ghosh, Anuradha; Akhtar, Mastura; Holderman, Chris; Zurek, Ludek (My University, 2014)
House flies are among the most important nonbiting insect pests of medical and veterinary importance. Larvae develop in decaying organic substrates and their survival strictly depends on an active microbial community. House flies have been implicated in the ecology and transmission of enterococci, including multi-antibiotic-resistant and virulent strains of Enterococcus faecalis. In this study, eight American Type Culture Collection type strains of enterococci including Enterococcus avium, Enterococcus casseliflavus, Enterococcus durans, Enterococcus hirae, Enterococcus mundtii, Enterococcus gallinarum, Enterococcus faecalis, and Enterococcus faecium were evaluated for their significance in the development of house flies from eggs to adults in bacterial feeding assays. Furthermore, the bacterial colonization of the gut of teneral flies as well as the importance of several virulence traits of E. faecalis in larval mortality was assessed. Overall survival of house flies (egg to adult) was significantly higher when grown with typically nonpathogenic enterococcal species such as E. hirae (76.0% survival), E. durans (64.0%), and E. avium (64.0%) compared with that with clinically important species E. faecalis (24.0%) and E. faecium (36.0%). However, no significant differences in survival of house fly larvae were detected when grown with E. faecalis strains carrying various virulence traits, including isogenic mutants of the human clinical isolate E. faecalis V583 with in-frame deletions of gelatinase, serine protease, and capsular polysaccharide serotype C. Enterococci were commonly detected in fly puparia (range: 75-100%; concentration: 10[superscript 3]–10[superscript 5] CFU/puparium) ; however, the prevalence of enterococci in teneral flies varied greatly: from 25.0 (E. casseliflavus) to 89.5% (E. hirae). In conclusion, depending on the species, enterococci variably support house fly larval development and colonize the gut of teneral adults. The human pathogenic species, E. faecalis and E. faecium, poorly support larval development and are likely acquired in nature by adult flies during feeding. House fly larvae do not appear to be a suitable model organism for assessment of enterococcal virulence traits.
Keywords: House fly; Enterococcus spp.; Larval development; Gut colonization